Intrauterine Deaths in North-Eastern Hungary with National and International Comparison - Singh Jashanjeet; Juhász Gábor; Tóth Zoltán; Póka Róbert (Journal of Preventive Medicine And Care, 2018)
Objective: Demographic analysis of intrauterine deaths in North-Eastern Hungary with national and international comparison. Materials and Methods: The authors collected data from the National Bureau of Statistics’ 1996-2014 database to assess frequency, gestational age, maternal age and education for six counties of the region. 722 individual cases were analyzed. A regional survey was initiated to collect more detailed data on living environment in the region between 2010 and 2014 through community midwifery services records. Results: Data over 20 years showed most intrauterine deaths (Perinatal mortality, Late fetal death, Stillbirth] occurred between 24th and 36th weeks of which 35% occurred in the North-Eastern region of Hungary. The causes of intrauterine deaths were placental abruption, cord accident, placental insufficiency, malformations and intrauterine infection. Detailed analysis regarding attendance at either the Obstetricians or the community midwifery services, the patient’s medical history and the patients’ compliance were reported, compliance in 1% completely lacked. Gravidity and multiparity were associated risk factors. A significant proportion was associated with teenage pregnancy, low maternal education, smoking risks, unemployment, dependence on social support, unhygienic environment and smaller accommodations. Lack of cooperation during antenatal care was significant. Conclusion: Frequency and distribution of intrauterine deaths in North-Eastern Hungary show a similar picture as those of socio-economic indices. The unfavorable trend came to an end in 2015, however the national statistics did not show any improvement. The solution to the problem seems to be independent of the service provision, therefore, socio-economic development of affected counties is warranted, and financial incentives and/or government aid provided during pregnancy may improve future perinatal outcomes.
Keywords: perinatal mortality